10–13 'A day in the life of…' an opportunity for students to experience a healthcare career. (17th November 2017) - Websdale, D; Major, D; Wright, D; Purva, M
Abstract : Introduction: There is an increasing demand for work experience placements in the NHS for school students which often exceeds available limits (Hillage et al., 2001). Research has also found that work experience prior to entry into nursing was a stimulus to them pursuing a career in nursing (Wells et al., 2000). Therefore the HILS team created two separate courses, A Day in the Life of a Doctor and Midwife which gave students the opportunity to increase their knowledge of their chosen career from medical student level through to fully qualified staff. The aim of these courses was to give students a valuable insight into the healthcare career they were considering and enable them to make the decision of it is a career they want to pursue. Methods: The one day courses were broken up into lectures in the morning and small group workshops in the afternoon. 57 students in total attended one of the two courses from 2014–2016.The course associated with doctors spent the first half of the day discussing medical school requirements, life as medical student, life as a junior doctor and simulation fellowship roles; bringing in doctors currently in these roles to share their experiences with the students. Day in the life of a midwife discussed university requirements, what to expect at interview and brought current student, community and hospital midwives in to expand on their roles. Some of the many workshops included airway/ultrasound, auscultation of the heart and resuscitation. Each course finished with a simulated scenario, using SimMan/SimMom as the patient and had students play roles such as student midwife or student anaesthetist. This allowed the students to practice some skills they had been shown in the workshops and assist the fully qualified staff while the rest of the students watched via video link. Results: 56 from 57 students agreed that by attending the course it helped them make the decision regarding their career. All pre/post course questions showed an increase in understanding on the Likert scale. Conclusion: The course has demonstrated a great balance between informative lectures and engaging workshops to help students make informed choices regarding their future careers; and this is supported by the significant improvement shown for each question asked on the pre/post course questionnaires. Further courses will be added this year to cover the demand but also to prevent over crowdedness which would negatively impact the students learning. There are plans in the future to expand our courses to cover other specialities such as Physiotherapy. References: Hillage, et al. Pre-16 work experience practice in England: An evaluation (Research Report RR263)2001. London: Department for Education and Employment. Wells, et al. Journal of Psychiatric and Mental Health Nursing2000;7(1):79–87.